THE IMPORTANCE OF HIGHER EDUCATION INSTITUTIONS FOR IMPROVING KEY COMPETENCES IN THE 21ST CENTURY IN THE REPUBLIC OF SERBIA - Sančanin, Branislav; Penjišević, Aleksandra; Simjanović, Dušan; Ranđelović, Branislav (Studies in Teaching and Education, 2024)
In a turbulent and increasingly demanding labor market, the gap between the demand for skilled workers and the supply of qualified job seekers is evident. The authors aimed to identify crucial competencies for the 21st century that should be actively developed in higher education institutions. The objective of this study was to identify key competencies that are targeted, planned, and systematically implemented in the education system. The research sample consisted of 137 participants from two private universities in the Republic of Serbia. The study found a strong correlation between certain competencies developed during studies and those developed independently of studies. Additionally, students with developed research skills exhibited greater information management skills. Factor analysis results supported the division of skills into two component groups. The first group, associated with static competencies, refers to an individual’s innate cognitive ability to effectively manage and understand various behaviors. The second group, associated with dynamic competencies, depends on external influences to ensure their effective application.